ROSTOVTZEFF, Mikhail Ivanovich. História de Roma. São Paulo: Zahar Editora S.A., 1983. (Revista de História da UEG (REVHIST), 2021)
Resenha da Obra: ROSTOVTZEFF, Mikhail Ivanovich. História de Roma. São Paulo: Zahar Editora S.A., 1983.